(untitled) (Research, Society and Development, 2023)
Rice has social, economic, and nutritional importance in different countries. In the integral form, its consumption confers more health benefits. However, due to its characteristics of greater hardness and prolonged cooking time, it has low acceptance among consumers. The objective of this study was to analyze, through a literature review, the methods that use physical principles to reduce the cooking time of brown rice. Sixty-nine studies found in different databases, published from 2002 to 2022, were selected. The characteristics of rice processing, its main forms of consumption, the nutritional superiority of brown rice, the challenges of production and the contextualization of rice were compiled in the development of new processing methods. The main processing methods found to reduce the cooking time of brown rice were described and analyzed in relation to investigation methods, physical principles and the results obtained. Being then the partial polishing; pre-hydration, cooking and drying; fissure induction; heating by infrared radiation; treatment with high hydrostatic pressure; ultrasonic treatment and low-pressure cold plasma treatment. It was found that although these methods reduce cooking time, some may cause a decrease in the nutritional value of brown rice. In this way, it was considered that the pre-hydration, cooking and drying treatments and the induction of fissuring in the grains are the most promising, since they significantly influenced the reduction of the cooking time of brown rice, without changing its nutritional value.